Identification of phytocomponents in the methanol extract Of cuscuta reflexa grown on nerium oleander Host plant through gc-ms analysis - POOJA SAINI; EKTA MENGHAN; REKHA MITHAL (International Journal of Pharma and Bio Sciences, 2017)
Medicinal plants are always been a great source for the search of new chemical entities having therapeutic potentials. Cuscuta reflexa is a parasitic plant with therapeutic potentials as antiviral, anticonvulsant activities, bradycardia, antisteroidogenic, antispasmodic and hemodynamic activities and also have an important place in Ayurveda. In the present piece of research work, attempts were made to identify different phytochemicals present in the methanol extract of Cuscuta reflexa grown on Nerium oleander host plant. GC-MS analysis of crude methanol extract was performed to identify different phytochemicals present in the Cuscuta reflexa. GC-MS is an advance technique for the identification of different chemical compounds present in the crude mixture of compounds. Pentanoic acid, 5-hydroxy-, 2, 4-di-t-butylphenyl esters, 1-Hexanol, 5-methyl-2-(1-methylethyl), Phthalic acid, isobutyl undecyl ester, Octadecanoic Acid and Celidoniol are compounds with major peaks in the GC-MS analysis. Most of these compounds are compounds with potentiality to cure various diseases. Cuscuta reflexa plant can be used for the isolation and characterization of new chemical compounds that can be used as future drugs against various life threatening diseases.